2018
DOI: 10.1007/s00382-018-4547-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model evaluation of the sensitivity of the global energy budget and hydrological cycle to resolution

Abstract: This study undertakes a multi-model comparison with the aim to describe and quantify systematic changes of the global energy and water budgets when the horizontal resolution of atmospheric models is increased and to identify common factors of these changes among models. To do so, we analyse an ensemble of twelve atmosphere-only and six coupled GCMs, with different model formulations and with resolutions spanning those of state-of-the-art coupled GCMs, i.e. from resolutions coarser than 100 km to resolutions fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 90 publications
(134 reference statements)
14
92
0
Order By: Relevance
“…Detailed descriptions of the atmospheric model differences, such as the impact of using MACv2-SP scheme, can be found in Vidale et al (2019a), and further assessments of ocean model differences up to 8 km resolution are described in Storkey et al (2018) and Mathiot et al (2019).…”
Section: Model Resolution Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed descriptions of the atmospheric model differences, such as the impact of using MACv2-SP scheme, can be found in Vidale et al (2019a), and further assessments of ocean model differences up to 8 km resolution are described in Storkey et al (2018) and Mathiot et al (2019).…”
Section: Model Resolution Differencesmentioning
confidence: 99%
“…For comparison, as shown in Vidale et al (2019a), the atmosphere-only simulations have a TOA which starts at around −1.5 W m −2 in 1950, with surface temperature of 288 K, OSR around 100-101 W m −2 and OLR around 240.5-241.5 W m −2 (which adjusts to around 239.5-240.5 W m −2 at 1980 when the TOA is closer to zero).…”
Section: Initial Spinup and Radiative Balancementioning
confidence: 99%
See 1 more Smart Citation
“…The latest multi‐model evaluation by Vannière et al . () shows a strengthening of the global hydrological cycle with increased model resolution by an increase in surface latent‐heat flux driven by more outgoing long‐wave radiation and less outgoing short‐wave radiation at the top of the atmosphere. This is because, globally, evaporation and precipitation are more sensitive to net surface short‐wave radiation (Wu et al ., ; ).…”
Section: Introductionmentioning
confidence: 99%
“…Demory et al (2014) have shown that increasing horizontal model resolution can significantly increase moisture convergence over land and, therefore, the local ratio of evaporation over precipitation. The latest multi-model evaluation by Vannière et al (2018) shows a strengthening of the global hydrological cycle with increased model resolution by an increase in surface latent-heat flux driven by more outgoing long-wave radiation and less outgoing short-wave radiation at the top of the atmosphere. This is because, globally, evaporation and precipitation are more sensitive to net surface short-wave radiation (Wu et al, 2010;2013).…”
Section: Introductionmentioning
confidence: 99%